Analysis of changes in the land use structure of developed and urban areas in Eastern Poland - Senetra Adam; Szczepańska Agnieszka; Wasilewicz-Pszczółkowska Monika (Bulletin of Geography. Socio-Economic Series)
The development of housing, services and industry as well as the accompanying infrastructure leads to the intensification of urbanisation processes and changes in land use structure. The area of land characterised by urban use is increasing. The above trend is also observed in Eastern Poland despite its predominantly rural character and the absence of metropolitan areas exerting great pressure on the local landscape, contributing to regional development and enhancing the region’s competitiveness. The paper discusses changes in land use structure in developed and urban areas in Eastern Poland. The analysis includes five Polish voivodeships (Lubelskie, Podkarpackie, Podlaskie, Świętokrzyskie and Warmińsko-Mazurskie) characterised by the lowest GDP per capita in the EU-25. For this reason, Eastern Poland will receive aid as part of the ‘Development of Eastern Poland’ Operational Program 2007-2013. This is the only supra-regional program in the European Union which promotes social and economic growth in underdeveloped regions by co-financing projects in urban development, road construction and tourism promotion. The analysis of changes in the share of developed and urban areas in total land area as well as changes in local land use structure (subgroups) covers the period of 2007-2013. The data relating to land use structure was supplied by the Head Office of Geodesy and Cartography. It was used to determine the scale and rate of urbanisation in the analysed voivodeships (regions) and their constituent poviats (counties) with special emphasis on suburban areas. The results were presented in the form of cartograms and thematic maps with the use of GIS tools. The GIS tools support the visualisation of the spatial distribution of the analysed phenomena.